West Sumatera curd effect on fecal IgA and IgG in BALB/c mice colon inflammation induced by dextran sodium sulphate - Utami, Diah Dwi; Yasmon, Andi; Heri Wibowo; Maya Ulfah; Ibnu Agus Ariyanto (Indonesian Journal of Biomedicine and Clinical Sciences, 2025)
Curd, a fermented buffalo milk product from West Sumatra, is known for its probiotic content. Probiotics are recognized for their health benefits, including potential advantages for inflammatory bowel disease (IBD). Previous studies have confirmed the probiotic status of curd. However, the effects of curd on the immunoglobulin response in colon inflammation are still not well understood. This study employs an experimental design to investigate the impact of curd on the levels of total immunoglobulins A (IgA) and G (IgG) in feces and analyze the correlation between total IgA levels in feces and IL-10 expression in serum and feces and total IgG levels in feces and TNF-α expression in serum and feces of BALB/c with colon inflammation. In the normal group, curd administration significantly increased total IgA levels in feces, indicating a potential modulation of the immune response. Conversely, in the inflammatory group, curd reduced total IgA levels, though this effect was not statistically significant. Similarly, while curd reduced total IgG levels in feces for both the normal and inflammatory groups, the reduction was not statistically significant. No significant relationships were found between total IgA levels in feces and IL-10 expression in serum and feces, nor between total IgG levels in feces and TNF-α expression in serum and feces.